Pelaksanaan Program Literasi Di SD Kota Pekanbaru - Nurdahlia Rahmadani; Sella Melani; Siti Alvia; Viona Grace Hutapea; Febrina Dafit (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Training is an important way to advance the quality of human resources. One of the goals of education is to produce human beings with character. Character building requires a long-term process, especially during the education period from elementary school (Putri & Romadhona, 2023). The purpose of this article is to (1) describe the concept of elementary school literacy, (2) describe the implementation of the elementary school literacy movement, (3) describe the problems of the elementary school literacy movement. This study uses research research methods. The sample was used by elementary school students from grades one to grade 6. The results obtained after the literacy program had a very positive impact on increasing children's learning and of course training children's literacy through fun and interesting activities. Therefore, it is very important for us to acquire literacy and learn reading skills as early as possible.